FUNÇÃO ESPERMÁTICA E REPRODUTIVA EM RATOS WISTAR EXPOSTOS AO BISFENOL A NO PERÍODO PRÉ-ADULTO - WISNIEWSKI, PATRICIA (2013)
Bisphenol A (BPA) is a monomer of polycarbonate plastic widely used in industry for the manufacture of packaging, epoxy resins and other materials. There are many effects previously seen as caused by BPA, among them testicular toxicity, reproductive changes in animal models and reports of human exposure to the chemical. The incomplete polymerization of BPA based products during manufacture and depolymerization induced by temperature’s change cause release of the compound and its derivatives into the environment and can be detected in canned foods, bottled liquids, in the air we breathe, and contaminant of rivers. In this research, we propose to test the hypothesis that BPA disrupts endocrine and reproductive systems. We evaluate the possible changes in 30 male wistar rats, in pre-adult phase, exposed for 40 days to 0mg/kg, 5mg/kg and 25mg/kg of BPA, and observe the evolution of body weight; testis and epididymis (divided into portions head, body and tail) weight; the mean concentration of sperm in the sample collected and sperm pathologies; the functionality of spermatozoon by observing mitochondrial activity, plasma membrane and acrosomal integrity; damage to the genetic material of the sperm; evaluation of sperm production, sperm reserves and sperm transit; we evaluated the sexual behavior and sexual orientation; and the hormonal profile in LH, FSH, testosterone and estradiol. The results observed were judged by statistical methods such as analysis of variance and comparison of means; Kruskal-Wallis test with comparisons by Freedman and Mann-Whitney tests. The parametric values were expressed as mean and standard error of the mean, and nonparametric data, as median and interquartile ranges. Statistical difference was considered when the p value was less than 0,05. We demonstrate that the product block the evolution of body weight; it alters the relative weight of the head and tail of the epididymis; it decreases the sperm concentration; it doesn’t alter morphology; it decreases mitochondrial activity in the sperm midpiece; it declines plasma membrane integrity of the sperm and decreases acrosome integrity; it does not cause changes in sperm DNA; it alters sexual orientation, by decreasing the preference for receptive females; it alters sexual behavior by decreasing latency to the first mount and intromission, and the number of ejaculations in a period; it declines daily sperm production and efficiency of spermatogenesis; it decreases sperm reserves; it slows the transit of epididymal spermatozoa; it declines hormones LH, FSH and testosterone in serum, and increases the hormone estradiol. We concluded that the product caused demasculinization of treated animals.